Neolithodes indicus Padate & Cubelio & Takeda 2020, sp. nov. - Padate, Vinay P.; Cubelio, Sherine Sonia; Takeda, Masatsune (Zenodo, 2020)
Neolithodes indicus sp. nov. (Figs. 1–5) Lithodes agassizii. — Anderson, 1896: 99.— Alcock & Anderson, 1899: 16.— MacGilchrist, 1905: 243.— Alcock, 1901: 232.— Alcock & MacGilchrist, 1905: pl. 68, 69 fig. 1 [Not N. agassizii (Smith, 1882)]. Neolithodes alcocki Dawson & Yaldwyn, 1985: 101.— Macpherson, 1988: 28 (remarks).— Dawson, 1989: 318. ( Nomen nudum ) Material examined. HOLOTYPE: Female (IO /SS/ANO/00094; CL 154.0 mm, PCL 140.0 mm, CW 151.0 mm), Arabian Sea, FORVSS stn 31602, 7.79°N, 76.46°E, 1324–1351 m, HSDT (CV), coll. Dr. Vinu Jacob, 15 July 2013. PARATYPES: Female (IO /SS/ANO/00095; CL 188.3 mm, PCL 182.0 mm, CW 169.7 mm), Arabian Sea, FORVSS stn 32701, 7.86°N, 76.41°E, 1060–1067 m, HSDT (CV), coll. Dr. Vinu Jacob, 25 July 2014; female (IO /SS/ANO/00096; CL 149.4 mm, PCL 140.9 mm, CW 152.9 mm), Arabian Sea, FORVSS stn 31909, 8.29°N, 76.03°E, 1275–1311 m, Expo net, coll. Dr. Vinu Jacob, 10 September 2013. Diagnosis. Carapace with numerous small secondary spinules on the carapace and pereopods in addition to the major spines. Cheliped dactyli with convex dorsal margins, rounded in cross section. Antennal peduncle with few, small, scattered granules or minute spinules, not distinctly spinose; scaphocerite simple. P2–4 meri compressed; flexor margin without large spines on P2–3, 4 spines on P4; extensor margin with several upright major spines protruding above level of secondary spines; pereopod 4 dactylus covered with spinules over surfaces of proximal four-fifths; ventral surfaces of coxae with blunt tubercles or granules. Description of holotype (IO/SS/ANO/00094). Carapace (Figs. 1A, 2) pyriform, glabrous, maximum width (excluding spines) subequal to length (0.98 PCL), becoming wider posteriorly; cervical and branchiocardiac grooves deep; gastric region more elevated than other regions, separated laterally from hepatic regions by shallow groove; cardiac region triangular, separated from gastric region by deep, wide groove; branchial regions inflated. Dorsal surface entirely covered with moderately dense short spinules; hepatic region with moderately large spine directed anterolaterally, margin between outer orbital spine and hepatic spine with 2 small spines; gastric region with 6 conical spines (slightly shorter than hepatic spine) arranged in a hexagon, and 1 short spine at centre of hexagon; each branchial region with 7 large and 6 small dorsal spines, branchial margin with 9 large and 8 small spines; cardiac region with 2 pairs of moderately large conical spines, and 1 small posterior spine; intestinal region with 1 pair of posteriorly directed large submedian spines, posterior carapace margin with 1 posteriorly directed median spine. Pterygostomial region evenly spinulose, bearing 1 small submarginal spine anteriorly. Rostrum (Figs. 1A, 2, 3) 0.1 PCL, trifid; median spine conical, inclined dorsally; divergent spines dorsal in position, obliquely directed, shorter than median spine, ventral surface convex with a forwardly directed proximal spine. Orbital margin unarmed. Outer orbital spine slender, not reaching level of cornea. Anterolateral spine shorter than outer orbital spine. Ocular peduncle (Fig. 3A) longer than cornea, bearing tubercles proximally; dorsal surface bearing 5 spinules, distalmost spinule largest. Cornea well-pigmented, positioned distoventrally on peduncle. Antennular peduncle consisting of 3 articles, extending beyond antennal peduncle by less than half length of article 3. Antennal peduncle (Fig. 3A) consisting of 5 articles; basal article bearing 1 small distolateral spinule; article 2 spinulose on dorsal and ventral surfaces, bearing 1 distal spinule dorsally; article 3 bearing 1 distolateral spine and 2 spines on ventral surface; article 4 more than half length of article 5, bearing 4 short subdistal spinules; article 5 cylindrical, bearing 10 scattered spinules, ventral spinules larger; scaphocerite a simple spine, shorter than article 4. Maxilliped 3 pediform, widely separated basally. Ischium with crista dentata consisting of 11 teeth and 1–2 spines on mesial surface; accessory tooth present. Merus with single row of setae on mesial margin. Carpus with mesial groove filled with setae. Propodus triangular in cross-section, with thick bunches of grooming setae on mesial margin, outer base of triangle with row of setae. Dactylus flattened with thick bunches of grooming setae along mesial margin. Thoracic sternite 5 with deep median fissure (Fig. 4A). Pereopod 1 (chelipeds) dimorphic but spination similar; surface of segments glabrous. Coxa with blunt tubercles and tufts of setae, unarmed. Ischiobasis with short conical spines ventrally, ischium with 2 larger spines ventro-distally. Merus dorsal and lateral surfaces spinose, longest spine distally; inner margin with 3 spines, second spine larger; ventral margin with short scattered conical spines. Carpus dorsal margin with 2 irregular rows of 5 slender spines; lateral margin with 2 irregular rows of 7 slender spines shorter than dorsal row; ventrally with small, scattered, acute tubercles. Palm with short conical spines on dorsal, lateral and ventral surfaces, inner surface with very short spines; dorsal margin with 2 irregular rows of 4 short conical spines; midlateral surface with 2 irregular rows of 4 spines shorter than dorsal spines, and a few scattered short spines; ventral surface with 2 rows of 5 spines, smaller than lateral and dorsal spines. Major cheliped 1.05 PCL; upper palm length 1.06 times height; occlusal margins corneous for distal one-thirds, proximally with 3 calcareous nodules; dactylus dorsal margin broadly convex, with rows of tufts of golden setae and proximal cluster of 4 small spines, 1.38 times longer than dorsal margin of palm. Minor cheliped 1.03 PCL; upper palm length 1.27 times height; occlusal margins corneous for more than distal half, proximally crenulate; dactylus dorsal margin broadly convex, with rows of tufts of golden setae and proximal cluster of 5 small spines, 2.04 times longer than dorsal margin of palm. Pereopods 2–4 (walking legs 1–3): Similar; segments spinose, surface between major spines glabrous; length increasing posteriorly, pereopod 4 longest. Distal margins of coxae bluntly spinose. Ischiobasis with short conical spines ventrally, ischium with 2 larger spines ventro-distally. Merus ovate in cross section, shorter than carapace; extensor margin with 6–7 major, in addition to long, paired distal spines; dorsal surface with row of 6–7 spines of similar length to proximal extensor spines (except on pereopod 4 merus with spine near midlength as long as cardiac carapace spines); flexor margins of P2–P3 with short spines only, that of P4 with short spines in addition to 2 irregular rows of 4 spines. Carpus slightly longer than half merus length; extensor margin with 6 spines, distal and third spines slightly longer than other spines; dorsal surface with 4 spines, distal and proximal spine longest. Propodus ovate to subcircular in cross section; with 8 or 9 spines on extensor margin and 8–10 similar spines on dorsal surface; flexor margin with 8–10 smaller spines. Dactylus curved, rounded in cross section, with 4 small proximal spines and several scattered spinules covering proximal half on P2, two-thirds on P3 and four-fifths on P4; apex corneous. P2 length 2.01 PCL. Merus 0.63 PCL; length: height ratio 4.60. Carpus 0.59 merus length. Propodus 0.90 merus length; length: height ratio 8.45. Dactylus 0.64 propodus length. P3 length 2.38 PCL. Merus 0.72 PCL; length: height ratio 4.48. Carpus 0.59 merus length. Propodus 0.97 merus length; length: height ratio 9.25. Dactylus 0.64 propodus length. P4 length 2.48 PCL. Merus 0.73 PCL; length: height ratio 4.31. Carpus 0.60 merus length. Propodus 1.07 merus length; length: height ratio 10.17. Dactylus 0.63 propodus length. P5 (Figs. 1A, 5) cylindrical, chelate, short (P5 length 0.57 PCL), setose, tucked under pleon; fingers spatulate. Pleon (Fig. 1B, 3B) asymmetrical. Somite 1 short, wide, bearing 2 transverse rows of sparsely placed minute tubercles. Somite 2 divided into 5 plates including median, 1 pair of sub-median and 1 pair of marginal plates; median plate bearing 4 large spines, 3–4 small spines and numerous evenly-spaced spinules; submedian plate bearing 4 large spines and numerous evenly-spaced spinules; marginal plates bearing prominent spines on distal and lateral margins. Somites 3–5 with well-developed plates as well as spinules embedded in membrane on right side, well-developed plates on left side, plates covered with evenly-spaced spinules; both margins of somite 3 as well as right margins of somites 4 and 5 bearing longer spines. Somite 6 short, sparsely spinulose, distal margin bearing 5 spinules. Telson semicircular, shorter than somite 6, sparsely spinulose. Pleopods 1 paired; pleopods 2–5 unpaired, left uniramous, pleopod 6 (= uropod) triangular, plate-like. Notes on paratypes . Larger female (IO /SS/ANO/00095). Carapace (Fig. 5A) longer than wide (CW 0.9 PCL); dorsal surface bearing short, conical primary spines, lighter in colour than surrounding carapace, spinules shorter than holotype; rostral spines very short (0.03 PCL); scaphocerite reduced; armature (spination) on chelipeds, pereopods and abdomen less prominent. Smaller female (IO /SS/ANO/00096). Carapace (Fig. 5B) slightly wider than long (CW 1.02 PCL); rostral spine short (0.06 PCL); armature on carapace and appendages similar to that of holotype. The larger paratype possesses relatively shorter rostral spines, scaphocerite, and armature on the carapace and appendages, as compared to the holotype and smaller paratype. The reduction of the armature on the carapace and appendages is generally known in lithodids (e.g., Ahyong 2010b) and the present new species is not exceptional in this regard. Major cheliped 1.10–1.28 PCL; upper palm length 1.09–1.06 times height; occlusal margins corneous for distal one-thirds, proximally with 3 calcareous nodules; dactylus dorsal margin broadly convex, with rows of tufts of golden setae and proximal cluster of 4 small spines, 1.49–1.53 times longer than dorsal margin of palm. Minor cheliped 1.08–1.25 PCL; upper palm length 1.30–1.19 times height; occlusal margins corneous for more than distal half, proximally crenulate; dactylus dorsal margin broadly convex, with rows of tufts of golden setae and proximal cluster of 5 small spines, 1.95–2.18 times longer than dorsal margin of palm. P2 length 1.85 PCL (small paratype; carpus, propodus and merus missing in large paratype). Merus 0.51–0.58 PCL; length: height ratio 4.00–4.47. Carpus 0.57 merus length. Propodus 0.90 merus length; length: height ratio 10.15. Dactylus 0.80 propodus length. P3 length 1.85–2.11 PCL. Merus 0.57–0.65 PCL; length: height ratio 4.52. Carpus 0.59–0.56 merus length. Propodus 1.01–0.97 merus length; length: height ratio 10.43–9.73. Dactylus 0.66–0.75 propodus length. P4 propodi and dactyli missing in both paratypes. Merus 0.58–0.63 PCL; length: height ratio 4.74–4.41. Carpus 0.63 merus length. Etymology . This species is named after the type locality, India. Gender is masculine. Remarks . Neolithodes indicus sp. nov. most closely resembles N. brodiei Dawson & Yaldwyn, 1970 from New Zealand, N. flindersi Ahyong, 2010a from southeastern Australia, and N. nipponensis Sakai, 1971 from Japan in the carapace bearing numerous secondary spines (in addition to major spines), a convex dorsal margin of the cheliped dactylus and P2–P4 with dorsoventrally compressed meri. The carapace and P1–P 4 in the new species differ from these congeners in possessing relatively less numerous, well-spaced secondary spinules (versus the carapace and appendages with more numerous, densely arranged small secondary spinules in N. brodiei (cf. Ahyong 2010a: figs. 43–47), N. flindersi (cf. Ahyong 2010b: figs. 1–3) and N. nipponensis (cf. Sakai 1971: fig. 1a, c). The rostrum (in specimens exceeding 80 mm PCL) of the new species (0.03–0.10 PCL) and N. nipponensis (“one twentieth” or 0.05 PCL) is proportionally shorter as compared to N. brodiei (0.12–0.28) and N. flindersi (0.10–0.19 PCL). The new species differs from its congeners in having a simple scaphocerite (versus the scaphocerite “often with bifid or trifid apex” in N. brodiei and N. flindersi (see Ahyong 2010a, figs. 44D, F–G; 2010b, fig. 3A–B), whereas it is “rudimentary, only represented by a few tiny spinules” in N. nipponensis (see Sakai 1971, fig. 1f). Ahyong (2010a) employed the armature of the pereopods 2–4 coxae and the configuration of the pereopods 2–4 meri as key characters differentiating N. brodiei and N. flindersi . The new species shares low blunt tubercles on P2–P4 coxae with N. brodiei , whereas N. flindersi possesses short, conical spines (in males and juvenile female). The new species differs from the latter three species in the lack of conspicuous spines on the flexor margins of the pereopods 2–3 meri. In the latter species, the pereopods 2–4 meri are armed with several conspicuous spines on the flexor margins, although the number and arrangement of those species are variable according to species and size (cf. Ahyong 2010a: figs. 43A, 46A, 47A–F for N. brodiei Ahyong 2010b: fig. 1A for N. flindersi Sakai 1971: pl. 8; Macpherson & Chan 2008: fig. 5a for N. nipponensis ). In the new species, the extensor margins of the pereopods 2–4 meri are lined with short, relatively well-spaced spines interspersed by 6–7 distinctly longer spines. In comparison, the pereopod 2–4 meri in N. brodiei are lined with closely-spaced short spines interspersed by 6–9 distinctly longer spines; in N. flindersi and N. nipponensis , the meral extensor spines are of similar size. The spinulation of the walking leg dactyli of the new species extends to the proximal half on P2, the proximal two-thirds on P3 and the proximal four-fifths on P4. In comparison, N. nipponensis has a longer extent of spinulation of the walking leg dactyli; in N. brodiei , the spinulation extends only slightly beyond the proximal half; in N. flindersi, the spinulation covers proximal half to three-quarters (Ahyong 2010a, b). The P4 propodus of the new species (only holotype, missing in paratypes) is comparatively stouter (propodus length: height ratio 7.1, 1.07 merus length). In comparison, in N. brodiei , the P4 propodus length: height ratio is 8.76–9.14 in males, and 8.03–9.33 in females; P4 propodus 0.89–0.93 merus length in males, and 0.98–1.03 in females. In N. flindersi , the P4 propodus length: height ratio is 9.67–12.27 in males, and 8.41–11.42 in females; P4 propodus 1.03–1.10 merus length in males, and 1.08–1.14 in females. MacGilchrist (1905) reported a female lithodid specimen (105 mm PCL, 93 mm CW) erroneously identified as L. agassizii from depths of 1000 fathoms (1829 m) in the north-eastern Arabian Sea (24.63°N, 62.04°E). This specimen, figured by Alcock & MacGilchrist (1905, pl. 68, 69 fig. 1), largely resembles the new species with regards to the pattern of spination of the carapace and the pereopods, but differs from the latter in having comparatively longer rostral spines, primary spines on the carapace dorsal margin, and major spines on P2–P4 meri. The above difference could be attributed to the age-related reduction in armature size. In view of the above-mentioned similarities, it is suggested that MacGilchrist’s specimen indeed represents the new species. The specimen, probably deposited in the collection of the Zoological Survey of India, Kolkata, was not available for examination. Neolithodes indicus sp. nov. was collected along with necrophage crustaceans such as the giant isopod Bathynomus keablei Lowry & Dempsey, 2006, and the carnivorous aristeid prawn Aristaeopsis edwardsiana (Johnson, 1868). Distribution . Arabian Sea, off the southwestern coast of India, at 1060–1351 m (present study), 406 fathoms (= 743 m) (Anderson 1896; Alcock 1901); northeastern Arabian Sea, 1829 m (MacGilchrist 1905). : Published as part of Padate, Vinay P., Cubelio, Sherine Sonia & Takeda, Masatsune, 2020, Description of a new species of deep-water king-crab (Crustacea: Decapoda Anomura) from the southeastern Arabian Sea, pp. 71-82 in Zootaxa 4845 (1) on pages 72-80, DOI: 10.11646/zootaxa.4845.1.5, http://zenodo.org/record/4406349 : {"references": ["Anderson, A. R. S. (1896) Natural history notes from the R. I. M. Survey Steamer ' Investigator, ' Commander C. F. Oldham, R. N., commanding. Series II. No. 21. An account of the deep sea Crustacea collected during the season 1894 - 95. Journal of the Asiatic Society of Bengal, 65 (2), 88 - 106.", "Alcock, A. & Anderson, A. R. S. (1899) Natural history notes from H. M. Royal Indian Marine Survey Ship ' Investigator, ' Commander T. H. Heming, R. N., commanding, Series III, No. 2. An account of the deep-sea Crustacea dredged during the surveying-season of 1897 - 98. Annals and Magazine of Natural History, Series 7, 3, 1 - 27. https: // doi. org / 10.1080 / 00222939908678071", "MacGilchrist, A. C. (1905) Natural history notes from the R. I. M. S. ' Investigator', Capt. T. H. Heming, R. N. (retired), commanding-Series III., No. 6. An account of the new and some of the rarer decapod Crustacea obtained during the surveying seasons 1901 - 1904. Annals and Magazine of Natural History, Series 7, 15, 233 - 268. https: // doi. org / 10.1080 / 03745480509443038", "Alcock, A. (1901) A descriptive catalogue of the Indian deep-sea Crustacea Decapoda Macrura and Anomala, in the Indian Museum. Being a revised account of the deep-sea species collected by the Royal Indian Marine Survey Ship Investigator. Trustees of the Indian Museum, Calcutta, iv + 286 pp., pls. 1 - 3. https: // doi. org / 10.5962 / bhl. title. 30840", "Alcock, A. & MacGilchrist, A. C. (1905) Crustacea. Part XI. In: Illustrations of the zoology of the Royal Indian Marine Surveying Steamer \" Investigator \". Trustees of the Indian Museum, Calcutta, pls. LXVIII-LXXVI.", "Smith, S. I. (1882) Reports on the results of dredging, under the supervision of Alexander Agassiz, on the East Coast of the United States, during the summer of 1880, by the U. S. Coast Survey Steamer \" Blake, \" Commander J. R. Bartlett, U. S. N., Commanding. XVII. - Report on the Crustacea. Part I. Decapoda. Bulletin of the Museum of Comparative Zoology at Harvard College, 10 (1), 1 - 104, pls. 1 - 14.", "Dawson, E. W. & Yaldwyn, J. C. (1985) King crabs of the world or the world of king crabs: an overview of identity and distribution-with illustrated diagnostic keys to the genera of the Lithodidae and to the species of Lithodes. In: Melteff, B. (Ed.), Proceedings of the International King Crab Symposium, Anchorage, Alaska, USA, 22 - 24 January 1985. University of Alaska, Anchorage, pp. 69 - 106.", "Macpherson, E. (1988) Revision of the family Lithodidae Samouelle, 1819 (Crustacea, Decapoda, Anomura) in the Atlantic Ocean. Monografias de Zoologia Marina, 2, 9 - 153.", "Dawson, E. W. (1989) King crabs of the world (Crustacea: Lithodidae) and their fisheries: A comprehensive bibliography. New Zealand Oceanographic Institute, Miscellaneous Publication, Division of water sciences, 101, 1 - 338.", "Ahyong, S. T. (2010 b) The marine fauna of New Zealand: king crabs of New Zealand, Australia and the Ross Sea (Crustacea: Decapoda: Lithodidae). NIWA Biodiversity Memoir, 123, 1 - 196. https: // doi. org / 10.11646 / zootaxa. 2362.1.3", "Dawson, E. W. & Yaldwyn, J. C. (1970) Diagnosis of a new species of Neolithodes (Crustacea: Anomura: Lithodidae) from New Zealand (note). New Zealand Journal of Marine and Freshwater Research, 4, 227 - 228. https: // doi. org / 10.1080 / 00288330.1970.9515341", "Ahyong, S. T. (2010 a) Neolithodes flindersi, a new species of king crab from southeastern Australia (Crustacea: Decapoda: Lithodidae). Zootaxa, 2362 (1), 55 - 62. https: // doi. org / 10.11646 / zootaxa. 2362.1.3", "Sakai, T. (1971) Illustrations of 15 species of crabs of the family Lithodidae, two of which are new to science. Researches on Crustacea, 4 - 5, 1 - 49, pls. I-XXI. https: // doi. org / 10.18353 / rcustacea. 4.5.0 _ 1", "Macpherson, E. & Chan, T. - Y. (2008) Some lithodid crabs (Crustacea: Decapoda: Lithodidae) from Taiwan and adjacent waters, with the description of one new species from Guam. Zootaxa, 1924 (1), 43 - 52. https: // doi. org / 10.11646 / zootaxa. 1924.1.2", "Lowry, J. K. & Dempsey, K. (2006) The giant deep-sea scavenger genus Bathynomus (Crustacea, Isopoda, Cirolanidae) in the Indo-West Pacific. In: Richer de Forges, B & Justine, J. L. (Eds.), Tropical Deep-Sea Benthos 24. Memoires du Museum national d'Histoire naturelle, 193, 163 - 192.", "Johnson, J. Y. (1868) Description of a new genus and a new species of macrurous decapod crustaceans, belonging to the Penaeidae, discovered at Madeira. Proceedings of the Zoological Society of London, 1867, 895 - 901."]}